Bioethical Issues in Antarctica - Iserson, Kenneth V. (Cambridge quarterly of healthcare ethics, 2021)
This paper describes the Antarctic environment, the mission and work setting at the U.S. research stations, the general population and living conditions, and the healthcare situation. It also dispels some common misconceptions that persist about this environment and about the scope and quality of medicine practiced there. The paper then describes specific ethical issues that arise in this environment, incorporating examples drawn from both the author’s experiences and those of his colleagues. The ethics of providing healthcare in resource-poor environments implies two related questions. The first is: What can we do with the available resources? This suggests that clinicians must not only know how to use all available equipment and supplies in the standard manner, but also that they must be willing and able to go beyond standard procedures and improvise, when necessary. The second question is: Of all the things we can do, which ones should we do? This paper addresses both questions in relation to Antarctic medical care. It describes the wide range of activities required of healthcare providers and some specific ethical issues that arise. Finally, it suggests some remedies to ameliorate some of those issues.